Prevalence and factors associated with hypertension among older people living with HIV in South Africa - Joshua Okyere; Castro Ayebeng; Bernard Afriyie Owusu; Kwamena Sekyi Dickson (BMC, 2022)
Abstract Background People living with HIV (PLHIV) are experiencing increased life expectancy mostly due to the success of anti-retroviral therapy. Consequently, they face the threat of chronic diseases attributed to ageing including hypertension. The risk of hypertension among PLHIV requires research attention particularly in South Africa where the prevalence of HIV is highest in Africa. We therefore examined the prevalence and factors associated with hypertension among older people living with HIV in South Africa. Methods We analysed cross-sectional data on 514 older PLHIV. Data were extracted from the WHO SAGE Well-Being of Older People Study (WOPS) (2011-2013). The outcome variable was hypertension status. Data was analysed using STATA Version 14. Chi-square and binary logistic regression were performed. The results were presented in odds ratio with its corresponding confidence interval. Results The prevalence of hypertension among PLHIV was 50.1%. Compared to PLHIV aged 50-59, those aged 60-69 [OR = 2.2; CI = 1.30,3.84], 70-79 years [OR = 2.8; CI = 1.37,5.82], and 80 + [OR = 4.9; CI = 1.68,14.05] had higher risk of hypertension. Females were more likely [OR = 5.5; CI = 2.67,11.12] than males to have hypertension. Persons ever diagnosed with stroke were more likely [OR = 3.3; CI = 1.04,10.65] to have hypertension when compared to their counterparts who have never been diagnosed with stroke. Compared to PLHIV who had no clinic visits, those who visited the clinic three to six times [OR = 5.3; CI = 1.35,21.01], or more than six times [OR = 5.5; CI = 1.41,21.41] were more likely to have hypertension. Conclusion More than half of South African older PLHIV are hypertensive. The factors associated with hypertension among older PLHIV are age, sex, ever diagnosed with stroke and number of times visited the clinic. Integration of hypertension management and advocacy in HIV care is urgently needed in South Africa in order to accelerate reductions in the prevalence of hypertension among older PLHIV, as well as enhance South Africa's capacity to attain the Sustainable Development Goal target 3.3.